Dexamethasone Induced Modulation of Reproduction: Investigating Role of Dexras1 Monomeric G Protein - Verma, Rashmi; Kumar, Navin; Thapliya, Ashish (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917714);" role="presentation">Many factors like hormonal, anatomical, genetic, and <span dir="ltr" style="left: calc(var(–scale-factor)*288.29px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916762);" role="presentation">environmental etc effect reproduction. Stressful <span dir="ltr" style="left: calc(var(–scale-factor)*481.90px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928268);" role="presentation">conditions <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.994667);" role="presentation">like <span dir="ltr" style="left: calc(var(–scale-factor)*90.50px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924281);" role="presentation">emotional-<span dir="ltr" style="left: calc(var(–scale-factor)*133.94px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929099);" role="presentation">stress, altered level of hormones etc can cause alterations in release of reproductive hormones <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951414);" role="presentation">thus ultimately effecting reproduction. In our study, we have focused to know the <span dir="ltr" style="left: calc(var(–scale-factor)*411.79px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945339);" role="presentation">modulation of reproduction <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909619);" role="presentation">induced by Dexamethasone <span dir="ltr" style="left: calc(var(–scale-factor)*188.09px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00629);" role="presentation">(DEX) <span dir="ltr" style="left: calc(var(–scale-factor)*219.05px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948807);" role="presentation">(a synthetic glucocorticoid), which mimics as a stress condition <span dir="ltr" style="left: calc(var(–scale-factor)*485.02px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951399);" role="presentation">in female <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917381);" role="presentation">mice <span dir="ltr" style="left: calc(var(–scale-factor)*98.54px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*120.24px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907567);" role="presentation">investigated <span dir="ltr" style="left: calc(var(–scale-factor)*175.75px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*195.29px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937235);" role="presentation">role <span dir="ltr" style="left: calc(var(–scale-factor)*218.05px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*233.51px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897716);" role="presentation">Dexras1 <span dir="ltr" style="left: calc(var(–scale-factor)*274.03px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01271);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*289.01px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922982);" role="presentation">reproduction <span dir="ltr" style="left: calc(var(–scale-factor)*347.71px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891631);" role="presentation">under <span dir="ltr" style="left: calc(var(–scale-factor)*377.67px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*397.09px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934546);" role="presentation">influence <span dir="ltr" style="left: calc(var(–scale-factor)*441.56px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*457.02px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879292);" role="presentation">Dexamethasone. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975095);" role="presentation">Glucocorticoid are known to <span dir="ltr" style="left: calc(var(–scale-factor)*196.37px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952876);" role="presentation">influence the release of <span dir="ltr" style="left: calc(var(–scale-factor)*298.87px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.988091);" role="presentation">GnRH hormone which in turn <span dir="ltr" style="left: calc(var(–scale-factor)*430.18px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940544);" role="presentation">regulate the release of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911933);" role="presentation">reproductive hormones <span dir="ltr" style="left: calc(var(–scale-factor)*168.14px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980445);" role="presentation">(LH, FSH)<span dir="ltr" style="left: calc(var(–scale-factor)*212.21px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900518);" role="presentation">. Dexamethasone is <span dir="ltr" style="left: calc(var(–scale-factor)*294.65px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911781);" role="presentation">reported to upregulates <span dir="ltr" style="left: calc(var(–scale-factor)*391.27px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897716);" role="presentation">Dexras1 <span dir="ltr" style="left: calc(var(–scale-factor)*427.78px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89442);" role="presentation">expression. So <span dir="ltr" style="left: calc(var(–scale-factor)*490.06px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901501);" role="presentation">we have <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*415.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905506);" role="presentation">investigated <span dir="ltr" style="left: calc(var(–scale-factor)*123.38px); top: calc(var(–scale-factor)*415.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93389);" role="presentation">the modulation of reproduction by alteration in the release o<span dir="ltr" style="left: calc(var(–scale-factor)*368.95px); top: calc(var(–scale-factor)*415.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935636);" role="presentation">f reproductive hormones LH and FSH <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971865);" role="presentation">under DEX dosage in female mice. <span dir="ltr" style="left: calc(var(–scale-factor)*230.69px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986229);" role="presentation">We observed that the level of hormones LH and FSH altered, in the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966213);" role="presentation">presence of Dexamethasone doses (0.1 and 0.5mg/kg mice). LH level is decreased while the level of FSH <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.870318);" role="presentation">increased <span dir="ltr" style="left: calc(var(–scale-factor)*115.94px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.998812);" role="presentation">with <span dir="ltr" style="left: calc(var(–scale-factor)*139.67px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00135);" role="presentation">DEX <span dir="ltr" style="left: calc(var(–scale-factor)*166.34px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.848444);" role="presentation">dose. <span dir="ltr" style="left: calc(var(–scale-factor)*193.37px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.863527);" role="presentation">So <span dir="ltr" style="left: calc(var(–scale-factor)*210.02px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*228.25px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.866217);" role="presentation">present <span dir="ltr" style="left: calc(var(–scale-factor)*263.14px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954422);" role="presentation">study reveals <span dir="ltr" style="left: calc(var(–scale-factor)*325.23px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*343.46px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937235);" role="presentation">role <span dir="ltr" style="left: calc(var(–scale-factor)*365.14px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*379.51px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883533);" role="presentation">Dexamethaso<span dir="ltr" style="left: calc(var(–scale-factor)*434.26px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.843184);" role="presentation">ne <span dir="ltr" style="left: calc(var(–scale-factor)*449.73px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*463.64px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920401);" role="presentation">modulat<span dir="ltr" style="left: calc(var(–scale-factor)*496.30px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96977);" role="presentation">ion <span dir="ltr" style="left: calc(var(–scale-factor)*515.23px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926961);" role="presentation">reproduction. It has been <span dir="ltr" style="left: calc(var(–scale-factor)*177.77px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927789);" role="presentation">reported earlier that Dexras1 is upregulated by Dexamethasone so we could <span dir="ltr" style="left: calc(var(–scale-factor)*493.54px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.856691);" role="presentation">suggest <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894722);" role="presentation">that <span dir="ltr" style="left: calc(var(–scale-factor)*89.66px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924037);" role="presentation">Dexras1 might <span dir="ltr" style="left: calc(var(–scale-factor)*151.82px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96612);" role="presentation">involve <span dir="ltr" style="left: calc(var(–scale-factor)*184.61px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9287);" role="presentation">in modulation of reproduction and could bec<span dir="ltr" style="left: calc(var(–scale-factor)*364.39px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913406);" role="presentation">ome a very important therapeutic target <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930255);" role="presentation">in reproduction <span dir="ltr" style="left: calc(var(–scale-factor)*135.86px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931897);" role="presentation">signaling <span dir="ltr" style="left: calc(var(–scale-factor)*174.98px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.846093);" role="presentation">processes.